2017
DOI: 10.3892/etm.2017.4027
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA ASncmtRNA-2 is upregulated in diabetic kidneys and high glucose-treated mesangial cells

Abstract: Abstract. Diabetic nephropathy (DN) is one of the most frequent complications associated with type I and II diabetes mellitus. Kidneys from patients with DN are characterized by mesangial matrix expansion and increased thickness of the glomerular basement membrane, which are induced by reactive oxygen species (ROS) production. Previous studies have been conducted to investigate this; however, the detailed mechanism of DN progression remains to be elucidated. The present study evaluated the expression of antise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…lncRNAs play important regulatory roles in the progression of DN. Gao et al proved that lncRNA-ASncmtRNA-2 is up-regulated in DN kidney tissues and HG-treated MCs, and its overexpression promotes the glomerular fibrosis in DN [29]. Li et al showed that lncRNA-1700020I14Rik contributes to the fibrosis of MMCs cultured with HG medium [30].…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs play important regulatory roles in the progression of DN. Gao et al proved that lncRNA-ASncmtRNA-2 is up-regulated in DN kidney tissues and HG-treated MCs, and its overexpression promotes the glomerular fibrosis in DN [29]. Li et al showed that lncRNA-1700020I14Rik contributes to the fibrosis of MMCs cultured with HG medium [30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ASncmtRNA-2 upregulation was accompanied by increase in TGFβ1 and its downstream gene, fibronectin . These authors have proposed that ROS mediated upregulation of ASncmtRNA-2 promotes DN through increased transcription of pro-fibrotic factors ( 33 ).…”
Section: Lncrnas and Diabetic Nephropathymentioning
confidence: 99%
“…It expresses in normal proliferating cells. Villegas et al, 2007;Burzio et al, 2009;Rivas et al, 2012;Villota et al, 2012;Vidaurre et al, 2014;Bianchessi et al, 2015;Gao Y. et al, 2017 SncmtRNA-2 (GenBank:…”
Section: Mtrna Modificationsmentioning
confidence: 99%
“…These two microRNAs target p16 and induce a cell cycle arrest at G2M phase, thereby affecting replicative senescence establishment (Bianchessi et al, 2015). Besides, ASncmtRNA-2 is also upregulated in diabetic kidneys and high glucosetreated mesangial cells and can promote glomerular fibrosis via modulating the expression of pro-fibrotic factors in diabetic nephropathy (Gao Y. et al, 2017).…”
Section: Lncrnas Mtdnamentioning
confidence: 99%